(untitled) (Journal of Organizational Psychology, 2020)
The Net Present Value of Benefits (NPVB) of installing mood uplifting paintings on hospital stay lengths were projected using a Cost- Benefits analysis. Net benefits were estimated from the "effect size” of mood uplift from Abstract Romanticism paintings and the average cost of hospital stay at 2,000/day. We used a nominal Social Discount Rate of 4% and a period of ten years. The analysis was conducted for a sample of hospitals and states. The results showed that installation of Abstract Romanticism paintings would have net benefits and this enhancement to the patient environment would likely result in substantial healthcare savings.